Evaluation of knowledge, attitude and practice towards cystic echinococcosis among undergraduate students in China - Yijie Xu; Chengkai Luo; Jiacheng Liu; Congwei Shen; Xingming Ma (PLoS ONE, 2025)
Background Cystic echinococcosis (CE), a zoonosis caused by Echinococcus granulosus sensu lato (EG), is a major public health burden in western China. The study aimed to evaluate the current status of KAP about CE among undergraduate students from western areas of China, and to provide a basis for developing health education strategies for college students on the prevention of CE. Methods A cross-sectional study was conducted from September 2023 to April 2024 in China. A cluster sampling method was used to enroll participants of undergraduate students. The Cronbach’s alpha coefficient of the questionnaire, the χ2 test for comparing rates, the independent sample T test for KAP scores, and linear regression analyses were conducted in the study. Results A total of 724 students were included in the study. Approximately 65% (471) of the participants were female students and 35% (253) were male students, and most of them were non-medical (90%) students and from rural areas (60%). The total score of KAP was from 21 to 57, and the mean score of KAP was 41.92±5.78, and less than one fifth of undergraduate students had higher level knowledge (14.8%), positive attitudes (15.5%), and low-risk practices (8.6%). The education level was a significant factor in predicting knowledge, and upper-year students (junior/senior) had a higher level of knowledge about CE than lower-year students (OR = 1.59, p = 0.01). Both residence (OR = 0.57, p < 0.05) and knowledge (OR = 2.26, p<0.05) were significant predicting attitude factors, and students with more knowledge had a positive attitude. But the significant predictors of practice were gender (OR = 3.26, p < 0.05), education level (OR = 0.75, p < 0.05) and attitude (OR = 2.25, p = 0.05). Conclusion The KAP level and pass rate for knowledge of CE among Chinese students in western areas is low, and most participants showed insufficient or poor CE knowledge. It is necessary to strengthen the health education in school or by multimedia communication platforms on CE for college students in western areas and those with identified related factors.